2021
DOI: 10.1111/acfi.12794
|View full text |Cite
|
Sign up to set email alerts
|

CEO religious university affiliation and financial reporting quality

Abstract: Utilising a novel proxy for CEO religiosity that is based on graduation from a religious university, we document evidence that a CEO's religiosity improves financial reporting quality. This effect is more pronounced when the firm is located in an area with higher geographical religiosity or more social capital, suggesting that a favourable environment facilitates the CEO religiosity effect. We also find that analyst forecasts are more accurate for firms led by a religious CEO, and that fewer analysts follow su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 104 publications
2
5
0
Order By: Relevance
“…A board that is knowledgeable about the company’s operations, risks, and financial reporting processes, and is actively engaged in overseeing those areas, is more likely to contribute to higher financial reporting quality and a shorter audit report lag. In this context our findings are consistent with the findings of [ 66 ] found that board independence and expertise are positively associated with financial reporting quality in China. Moreover, from the agency’s perspective, all the conflicts are resolved timely, and the decision will be acute that releasing the accounts early increase the financial reporting quality and findings consistent with the agency theory perspective.…”
Section: Discussion On Findingssupporting
confidence: 92%
“…A board that is knowledgeable about the company’s operations, risks, and financial reporting processes, and is actively engaged in overseeing those areas, is more likely to contribute to higher financial reporting quality and a shorter audit report lag. In this context our findings are consistent with the findings of [ 66 ] found that board independence and expertise are positively associated with financial reporting quality in China. Moreover, from the agency’s perspective, all the conflicts are resolved timely, and the decision will be acute that releasing the accounts early increase the financial reporting quality and findings consistent with the agency theory perspective.…”
Section: Discussion On Findingssupporting
confidence: 92%
“…In other studies, firm religiosity has been determined through the personal religious views of the firm's top executives (Adhikari & Agrawal, 2016;Chen et al, 2022;Harjoto & Rossi, 2019;Liao et al, 2019). While alleviating the problem of inference, the use of executive characteristics may overestimate the role of managerial values and beliefs on corporate culture.…”
Section: Is Corporate Social Responsibility (Csr) Influenced By Relig...mentioning
confidence: 99%
“…In contrast to the prior literature, we employ a novel measure of religiosity which directly reflects firm‐level adherence to Christian values and a biblical worldview. In previous studies, religious influence on firms has been proxied either by geographical, typically county‐level measures of religiosity in the proximity of the corporate headquarters (e.g., Adhikari & Agrawal, 2016; Chantziaras et al, 2020; Cui et al, 2015; Du et al, 2014; Rossi et al, 2019) or by inferring the personal religious views of the firm's top executives (Adhikari & Agrawal, 2016; Chen et al, 2022; Chen, Chen, et al, 2021; Harjoto & Rossi, 2019; Liao et al, 2019). Arguably, these measures are rather indirect proxies of religiousness, which may not be an accurate representation of a firm's internal culture and adherence to religious values.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank an anonymous reviewer for highlighting the possible limitations of the GPG calculation, as suggested byChen et al (2022) for a similar proxy. Unfortunately, information on compensation for individual employees is not available.…”
mentioning
confidence: 99%